"'Mid wastes interminably spread": Wordsworth's and Coleridge's Inoperative Communities. Issue 2 (4th March 2021) - Sargent, Andrew
ABSTRACT: This essay puts Wordsworth's Salisbury Plain in dialogue with Coleridge's Rime of the Ancyent Marinere in order to explore the two poets' investment in what Jean-Luc Nancy would call "inoperative communities, " a notion of "community without community" that thinks the political and political agency beyond the binary of praxis and the philosophical quietism that critics often ascribe to Wordsworth's major works. As wanderers on the margins of the social, Coleridge's Mariner and Wordsworth's "characterless" figures cast storytelling as a de-subjectivizing force that communicates non-closure and erodes self-mastery. By formally portraying normative aesthetic and political markers such as community, character, agency, and narrative as non-totalizing and inoperative, these poems gesture toward the notion of a shapeless, ungrounded community whose members fall between the cracks of reified political and literary structures. Because Coleridge's poem formally and thematically revisits the inoperative energies of Wordsworth's earlier text, this essay posits that the Rime 's presence in the first edition of the Lyrical Ballads —Romanticism's so-called annus mirabilis —heralds an alternate trajectory of romanticism beyond the high Romantic humanism of the volume's closing poem "Tintern Abbey."